The e-Posyandu Health Application (ePoK) as a medium to enhance parental independence in stimulating growth and development of children under five - Melly Damayanti; Nurul Aini Suria Saputri; Darwitri Darwitri (Healthcare in Low-resource Settings)
The early childhood period, specifically from birth to five years of age, represents a crucial phase for growth and development. However, stunting prevalence worldwide remains high. Parental independence in stimulating children under five’s growth and development is pivotal in addressing this issue. The study aims to explore the impact of the e-Posyandu Health Application (ePoK) in promoting parental independence in the growth and development of their children. The research employed a quasi-experimental method with a pre-posttest control group design. The sample consisted of 140 parents with children under five years old in Tanjungpinang City, divided into intervention (70 parents) and control (70 parents) groups. The intervention group used the ePoK application for 3 months, while the control group received routine puskesmas (community health center) services. Data collection used a parental independence questionnaire. The intervention group showed a significant 23% increase in mean independence scores (p=0.001), compared to no significant changes in the control group. After the intervention, a meaningful difference between groups was observed (p=0.001). Multiple regression analysis revealed education, knowledge, skills, and motivation as significant predictors, explaining 58.4% of the variation in independence (adjusted R2=0.584). Based on our findings, the ePoK application effectively enhances parental independence by stimulating the growth and development of children under five. The application can be a supportive tool for parents to monitor and optimize child development independently.